Interpretation of Peripheral Arterial and Venous Doppler Waveforms: A Consensus Statement From the Society for Vascular Medicine and Society for Vascular Ultrasound. Issue 3 (September 2020) - Kim, Esther S. H.; Sharma, Aditya M.; Scissons, Robert; Dawson, David; Eberhardt, Robert T.; Gerhard-Herman, Marie; Hughes, Joseph P.; Knight, Steve; Kupinski, Ann Marie; Mahe, Guillaume; Neumyer, Marsha; Poe, Patricia; et al.
This expert consensus statement on the interpretation of peripheral arterial and venous spectral Doppler waveforms was jointly commissioned by the Society for Vascular Medicine (SVM) and the Society for Vascular Ultrasound (SVU). The consensus statement proposes a standardized nomenclature for arterial and venous spectral Doppler waveforms using a framework of key major descriptors and additional modifier terms. These key major descriptors and additional modifier terms are presented alongside representative Doppler waveforms, and nomenclature tables provide context by listing previous alternate terms to be replaced by the new major descriptors and modifiers. Finally, the document reviews Doppler waveform alterations with physiologic changes and disease states, provides optimization techniques for waveform acquisition and display, and provides practical guidance for incorporating the proposed nomenclature into the final interpretation report.